Conserved nucleation sites reinforce the significance of Phi value analysis in protein‐folding studies. Issue 7 (18th July 2014) - Gianni, Stefano; Jemth, Per
Abstract The only experimental strategy to address the structure of folding transition states, the so‐called Φ value analysis, relies on the synergy between site directed mutagenesis and the measurement of reaction kinetics. Despite its importance, the Φ value analysis has been often criticized and its power to pinpoint structural information has been questioned. In this hypothesis, we demonstrate that comparing the Φ values between proteins not only allows highlighting the robustness of folding pathways but also provides per se a strong validation of the method. © 2014 IUBMB Life, 66(7):449–452, 2014